Innovation in Islamic Philosophy Teaching Methods Perspectives of the Al-Diniy Al-‘Aqlaniy School of Educational Philosophy - Muhlisin, Muzdakir (Medina-te : Jurnal Studi Islam, 2026)
This study analyses how innovations in philosophy teaching methods contribute to the quality of learning outcomes in the Islamic Philosophy course at the Faculty of Ushuluddin, Adab and Humanities, State Islamic University of Salatiga, reviewed from the perspective of Al-Diniy Al-‘aqlaniy's philosophy of education. This qualitative study uses a case study approach. Data collection techniques included interviews, observation, and documentation. The data obtained were analysed using category aggregation and direct interpretation techniques. The results of the study show that innovation in learning methods is an important aspect in realising quality education. Furthermore, this study reveals that various innovative philosophy teaching methods, such as group discussions, text studies, recitations, open dialogues, and empirical observations, have proven to be quite effective in meeting learning outcomes. Innovative teaching methods are a form of responsibility in carrying out teaching and learning activities so that these activities can be organised and run effectively, thereby ensuring that the material presented is well received and the learning objectives are achieved.